Effects of boxing exercise in people with Parkinson’s disease: a systematic review - Wang, Zhihai; Song, Baofu; Liu, Cong; Ma, Huihui; Bai, Zirong; Carneiro, Marcelo A. S.; Youssef, Layale; Chen, Chao; Zhang, Lingli; Wang, Dan; Wang, Dexin (Frontiers in Aging Neuroscience, 2025)
ObjectiveParkinson’s disease (PD) is a chronic neurodegenerative disorder characterized by progressive changes in both motor and non-motor symptoms. Boxing exercise can improve PD symptoms. This review aimed to determine the effects of boxing exercise on lower extremity strength, balance, mobility, gait, depression, quality of life, disease severity, exercise safety, and adherence in patients with PD.DesignA systematic review.Setting and participantsArticles were selected if they included participants diagnosed with PD and used boxing exercise as the main intervention.MethodsSystematic review study based on PRISMA criteria. Searches were implemented in PubMed, EMBASE, Web of Science, and Cochrane Library until February 2024. We selected studies reporting on the pre-post assessment of a boxing intervention with lower extremity strength, balance, mobility, gait, depression, quality of life, disease severity, exercise safety, and adherence in patients with PD. Two independent reviewers conducted study selection, data extraction, and quality assessment. The Physiotherapy Evidence Database and ROBINS-I 2.0 criteria evaluated the literature’s quality.ResultsOut of 4,301 records, 13 studies were included, involving 402 PD patients aged 53–89, with 72.4% being male. Interventions lasted 6–96 weeks, primarily in community settings and gymnasiums. Moderate-quality evidence suggested boxing exercises is feasible and effective for enhancing lower extremity strength, balance, mobility, gait, depression, quality of life, disease severity, exercise safety and adherence in PD patients.Conclusions and implicationsBoxing exercise can effectively improve both motor and non-motor symptoms in PD patients, with safety and high adherence. This review systematically summarizes the emerging evidence on the application of boxing exercise in the rehabilitation of patients with PD. Future research should include more homogenous PD patient populations and conducting randomized controlled trials.